(untitled) (Malay Literature, 2013)
Mir’at al-Tullab by Syeikh Abdul Rauf Singkel is one of the masterpieces in the history of Malay writing in Aceh. The work written in 1661 demonstrates knowledge of Shari’ah law including the subjects on commercial law, matrimonial law and criminal law. The major idea that runs through the whole work is that of the role of sultan and ulama in preserving Islamic laws of the state. The importance of Mir’at al-Tullab is reflected in the large number of manuscripts that are available. In spite of its importance, there is still a lack of studies of the work especially those based on several Jawi manuscripts that are known to exist in Leiden University Library. This article is a preliminary study of five manuscripts of Mir’at al-Tullab kept in the Special Collections, Leiden University Library, and to identify basic features of the Islamic laws in Aceh in the mid-seventeenth century based on the manuscripts. Mir’at al-Tullab portray an early example of the implementation of Islamic law in Aceh as to replace the adat law practices that existed before. Keywords: Mir’at al-Tullab, Syeikh Abdul Rauf Singkel, history of Malay, Islamic law, manuscripts